Nigeria school feeding program: Baseline data collection training manual for enumerators - Andam, Kwaw S.; Amare, Mulubrhan; Gelli, Aulo; Kosec, Katrina; Abay, Kibrom A.; Bamiwuye, Temilolu; Fasoranti, Adetunji (International Food Policy Research Institute, 2024)
School feeding programs have emerged as promising multi-sectoral interventions that not only provide food to 368 million children annually, but could also improve diets, stimulate agricultural productivity for smallholders, and increase their incomes through "home-grown" school feeding procurement models. There is limited rigorous evidence on the effects of smallholder participation in school feeding markets and the trade-offs within different pro-smallholder procurement approaches. In parallel, many smallholders in Africa face market constraints and lack market orientation for commercializing production. The impact evaluation (IE) of the home-grown school feeding program on smallholder sales and revenues: an effectiveness trial in Osun State, Nigeria is a one-year (2023 – 2024) form project implemented by IFPRI and other key stakeholders including the World Food Programme (WFP). The IE will randomly select schools from which the cooks in the selected schools will receive training (the treatment group) and those from schools in non-participant areas that receive no training. The IE will evaluate key outcomes related to the proportion of smallholder farmers selling their agricultural products to schools as well as to traditional markets; farmers’ sales volume of locally grown agricultural outputs to both the market and schools (cooks); farmers’ sales revenue from locally produced agricultural outputs to both the market and cooks; cost per unit of school meal to schools and cooks; menu quality and quantity assessment; awareness of food safety and accessibility to fresh produce; subjective evaluation of hygiene standards; empowerment and well-being initiatives for women.